Pituitary apoplexy: a rare cause of middle cerebral artery infarction - Hassan, Radhiana; Sharis Osman, Syazarina; Mohamed Mukari, Shahizon Azura; Abu Bakar, Azizi (Malaysian Medical Associations, 2013)
Pituitary apoplexy is a well-known complication of a pituitary adenoma. However, an ischaemic event caused by pituitary apoplexy is rare. We reported a case of pituitary apoplexy with middle cerebral artery infarction in a 44-year old man who presented with a sudden onset of altered sensorium. Vasospasm is the most likely underlying cause of the infarction in this case secondary to transdiaphragmatic rupture of the sella tumour into the subarachnoid space.